9x+2y+17+10x-12y-11=

Simple and best practice solution for 9x+2y+17+10x-12y-11= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+2y+17+10x-12y-11= equation:


Simplifying
9x + 2y + 17 + 10x + -12y + -11 = 0

Reorder the terms:
17 + -11 + 9x + 10x + 2y + -12y = 0

Combine like terms: 17 + -11 = 6
6 + 9x + 10x + 2y + -12y = 0

Combine like terms: 9x + 10x = 19x
6 + 19x + 2y + -12y = 0

Combine like terms: 2y + -12y = -10y
6 + 19x + -10y = 0

Solving
6 + 19x + -10y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + 19x + -6 + -10y = 0 + -6

Reorder the terms:
6 + -6 + 19x + -10y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 19x + -10y = 0 + -6
19x + -10y = 0 + -6

Combine like terms: 0 + -6 = -6
19x + -10y = -6

Add '10y' to each side of the equation.
19x + -10y + 10y = -6 + 10y

Combine like terms: -10y + 10y = 0
19x + 0 = -6 + 10y
19x = -6 + 10y

Divide each side by '19'.
x = -0.3157894737 + 0.5263157895y

Simplifying
x = -0.3157894737 + 0.5263157895y

See similar equations:

| 63.00+x=67.40 | | 9x-2*(-5+7)=-8x-5 | | -4(4n+3)=8 | | 3x-6+2=5x-6 | | 3x=26.25 | | 5(x+4)=3(2x-1) | | .7(.1x+.1)=-.7 | | 14(v+2)-2v=4(3v+3)-18 | | x+31=-48 | | (3x-1)(2x^2+3x-3)=0 | | 9.5-23.5p=3.5(9p+3) | | (5v-6)(5+v)=0 | | 10x+6y+6+17x-16y-16= | | 4(y+3)-3=25 | | 11(z+1)-3(z-1)=3(z-2)+4(z-3) | | 9x-2(-5+7)=-8x-5 | | 4(9-14)=n-3 | | 67-5*7= | | (x+1)3=216 | | -0.04x^2+0.64x+1.94=0 | | (3x-2)(2x+6)=0 | | 9x-(8x+9)=9x-33 | | 30y+8=32 | | (2-x)(2+x)=0 | | 5=9x-8x+6 | | (7-x)(x^2+2x-3)=0 | | 6(6-4)=12y | | x+27=-52 | | x^2=128-8x | | 11x^2+2x=10 | | (7a^2-2a+6)-(-5a^2+3)=0 | | 3x+8(x-1)=0 |

Equations solver categories